Attilâ İlhan’s Anti-Cosmopolitanism - Burcu Alkan (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Attilâ İlhan (1925-2005) was an active public intellectual and a prolific author who wrote poems, novels, essays, and screenplays. While his poetics are marked by his distinct romantic style, his novelistic writing follows a strong social realist line. With his enthusiasm for Atatürk’s national revolution, his interest in the Ottoman culture, and his Marxist formation, he emphasises the importance of a “national culture synthesis” in his essays. He builds this idea of “national culture synthesis” in opposition to the so-called universal values of cosmopolitanism. This article discusses İlhan’s anticosmopolitanism as such in the light of the current theories of critical cosmopolitanism. While İlhan argues against “compradorial cosmopolites” in his essays, his anticosmopolitanism is rather prominent in his novels as well. Set in major cities, the novels celebrate the diversity and dynamism of their cityscapes. However, his depiction of such diversity exposes the ambivalences underneath his anti-cosmopolitanism. The article first provides a parallel reading of two contemporaries, Attilâ İlhan and Frantz Fanon, on national consciousness and cosmopolitanism. Then it focuses on İlhan’s Zenciler Birbirine Benzemez as a case study. Finally, it extrapolates upon the problems of his anti-cosmopolitanism within his broader literary oeuvre.